(untitled) (Journal of actual problems of jurisprudence, 2019)
This article describes the political situation during the era of statesman - Little Horde Abulhair Khan, as well as military, diplomatic, legal relationship with neighboring countries. Keywords: military and diplomatic relations, political and legal status, military qualities, diplomatic activity, political choice.